Lateral Condyle Fracture of the Humerus in Children Treated with Bioabsorbable Materials. (9th October 2013) - Andrey, Véronique; Tercier, Stéphane; Vauclair, Frédéric; Bregou-Bourgeois, Aline; Lutz, Nicolas; Zambelli, Pierre-Yves
Abstract : The aim of this study was to compare clinical and radiological outcome of lateral condyle fracture of the elbow in children treated with bioabsorbable or metallic material. From January 2008 to December 2009, 16 children with similar fractures and ages were grouped according to the fixation material used. Children were seen at 3, 6, and 12 months and more than 4 years (mean 51.8 months) postoperatively. The clinical results were compared using the Mayo Elbow Performance Score (MEPS). Radiographic studies of the fractured and opposite elbow were assessed at last follow-up control. Twelve children had a sufficient followup and could be included in the study. Seven could be included in the traditional group and 5 in the bioabsorbable group. At 12 months, the MEPS was 100 for every child in both groups. Asymptomatic bony radiolucent visible tracks and heterotopic ossifications were noted in both groups. There were no significant differences in terms of clinical and radiological outcome between the two groups. The use of bioabsorbable pins or screws is a reasonable alternative to the traditional use of metallic materials for the treatment of lateral condyle fracture of the elbow in children.